Kebanggaan Berbahasa (Linguistic Pride) Pada Masyarakat - Banun Binaningrum (Ushuluna: Jurnal Ilmu Ushuluddin, 2015)
Linguistic pride is condition where someone or a group of society fell comfort in using a language that they choose and use to communicate with other in their groups. Discussing of linguistic pride, has close relation to the attitude of language. There are 3 positive characteristics of language attitude: Lingusitic pride, the awareness of language norm, and language loyalty. These three positive characteristics are crucial factors for the success in the efforts of language preservation in facing any external pressures to the society as the owner of language who actually has more dominant influence may describe their linguistic pride of the language. language attitude refers to any kind of behaviour to the language and how the language is behaved by the society. includes the attitude in planning and preserving the language. Language contact which includes in it; the switching code and mixing code may influence the linguistic pride of the society. When someone mostly use both of switching and mixing code in his/her communication, it may describe his/her to the language the used. Language dominance is another thing that may influence the linguistic pride. In multilingual society, the language dominance may occur when each group do not respect each other and do not preserve their language. Tp avoid the dominance of language especially in multilingual society, it is important to put and use the language of each group in proper situation and place in accordance with the agreement among each groups in the society. Language dominance has close relation to the linguistic power and linguistic force. And both of them can measured by some indicators, i.e: Demography. Spreadness, Economy, Ideology, and Culture, the factors of language attitude, Language contact, and Language dominance are the crucial factors that can describe the linguistic pride may also influence to the genociidng of language. All of those, of course is determined by the users of the language itself and their efforts to preserve their language.